2013
DOI: 10.1111/add.12114
|View full text |Cite
|
Sign up to set email alerts
|

A comparison among tapentadol tamper‐resistant formulations (TRF) and OxyContin® (non‐TRF) in prescription opioid abusers

Abstract: Aims To examine whether tamper-resistant formulations (TRFs) of tapentadol hydrochloride ER 50 mg (TAP50) and tapentadol hydrochloride 250 mg (TAP250) could be converted into forms amenable to intranasal (Study 1) or intravenous abuse (Study 2). Design Randomized, repeated-measures study designs were employed. A non-TRF of OxyContin® 40 mg (OXY40) served as a positive control. No drug was taken in either study. Setting The studies took place in an outpatient setting in New York, NY. Participants 25 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…90 A tamper-resistant formulation of tapentadol PR (which is resistant to crushing and forms a gel when combined with small volumes of liquid) is available in the United States. 91 Although caution is warranted when prescribing tapentadol PR to patients for whom there is a concern about an elevated risk of drug misuse, abuse, addiction, or diversion, 33 results of recent studies indicate a low level of abuse for tapentadol in practice. In a study 92 that evaluated the rates of abuse and diversion of tapentadol IR after its introduction to the US market using data from a US surveillance system (the Researched Abuse, Diversion, and AddictionRelated Surveillance [RADARS] system 93 ), rates of tapentadol IR abuse and diversion were low during the first 24 months after its introduction (Figure 8).…”
Section: Abuse and Diversionmentioning
confidence: 99%
“…90 A tamper-resistant formulation of tapentadol PR (which is resistant to crushing and forms a gel when combined with small volumes of liquid) is available in the United States. 91 Although caution is warranted when prescribing tapentadol PR to patients for whom there is a concern about an elevated risk of drug misuse, abuse, addiction, or diversion, 33 results of recent studies indicate a low level of abuse for tapentadol in practice. In a study 92 that evaluated the rates of abuse and diversion of tapentadol IR after its introduction to the US market using data from a US surveillance system (the Researched Abuse, Diversion, and AddictionRelated Surveillance [RADARS] system 93 ), rates of tapentadol IR abuse and diversion were low during the first 24 months after its introduction (Figure 8).…”
Section: Abuse and Diversionmentioning
confidence: 99%
“…For example, a tamper-resistant formulation of Nucynta® ER was compared against an original non-tamper resistant formulation of Oxycontin® to determine ease of reducing each product's particle size [15]. Crushed products produced from each tablet by experienced abusers using any equipment they desired was ultimately passed through varying sieves for particle size analysis.…”
Section: Particle Size Reduction Studiesmentioning
confidence: 99%
“…A comparison of two formulations of oxymorphone found that the maximum time participants were willing to spend tampering with the products was approximately 15 minutes (10). In a similar study, participants spent an average of 3 to 7 minutes to manipulate oxycodone or tapentadol for intranasal or intravenous administration even though they were allowed up to 60 minutes (11). The latest report from the Researched Abuse, Diversion and Addiction-Related Surveillance (RADARS) system showed that ease of manipulation was a main factor for a strong preference for IR over ER opioids (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Category 1 studies that focus on the "output" of the manipulation effort, the ALERRT instrument was developed to capture information about the "input" (time, effort, and resources necessary to convert the product into an abusable form). If the degree of effort required is perceived by drug users to be onerous, it is possible that this property may in and of itself deter abuse (9,11). In this respect, it is important to note that this dimension is not captured in Category 3 clinical studies designed to evaluate the abuse potential of a new drug.…”
Section: Introductionmentioning
confidence: 99%